The Calcium-Dependent Protein Kinase CPK28 Regulates Development by Inducing Growth Phase-Specific, Spatially Restricted Alterations in Jasmonic Acid Levels Independent of Defense Responses in Arabidopsis. Issue 3 (3rd March 2015) - Matschi, Susanne; Hake, Katharina; Herde, Marco; Hause, Bettina; Romeis, Tina
Abstract : A calcium-dependent protein kinase plays dual roles, maintaining tissue-specific phytohormone levels in adult plants without affecting defense responses and regulating defense signaling in seedlings. Abstract: Phytohormones play an important role in development and stress adaptations in plants, and several interacting hormonal pathways have been suggested to accomplish fine-tuning of stress responses at the expense of growth. This work describes the role played by the CALCIUM-DEPENDENT PROTEIN KINASE CPK28 in balancing phytohormone-mediated development in Arabidopsis thaliana, specifically during generative growth. cpk28 mutants exhibit growth reduction solely as adult plants, coinciding with altered balance of the phytohormones jasmonic acid (JA ) and gibberellic acid (GA ). JA -dependent gene expression and the levels of several JA metabolites were elevated in a growth phase-dependent manner in cpk28, and accumulation of JA metabolites was confined locally to the central rosette tissue. No elevated resistance toward herbivores or necrotrophic pathogens was detected for cpk28 plants, either on the whole-plant level or specifically within the tissue displaying elevated JA levels. Abolishment of JA biosynthesis or JA signaling led to a full reversion of the cpk28 growth phenotype, while modification of GA signaling did not. Our data identify CPK28 as a growth phase-dependent key negative regulator of distinct processes: While in seedlings, CPK28 regulates reactive oxygen species-mediated defense signaling; in adult plants, CPK28 confers developmental processes by the tissue-specific balance of JA and GA without affecting JA -mediated defense responses.